A preliminary study of phosphodiesterases and adenylyl cyclase signaling pathway on red blood cell deformability of sickle cell patients - Goksel, Evrim; Ugurel, Elif; Nader, Elie; Boisson, Camille; Muniansi, Ingrid; Joly, Philippe; Renoux, Celine; Gauthier, Alexandra; Connes, Philippe; Yalcin, Ozlem (Frontiers in Physiology, 2023)
Sickle cell disease (SCD) is an inherited hemoglobinopathy characterized by chronic anemia, intravascular hemolysis, and the occurrence of vaso-occlusive crises due to the mechanical obstruction of the microcirculation by poorly deformable red blood cells (RBCs). RBC deformability is a key factor in the pathogenesis of SCD, and is affected by various factors. In this study, we investigated the effects of adenylyl cyclase (AC) signaling pathway modulation and different phosphodiesterase (PDE) modulatory molecules on the deformability and mechanical stress responses of RBC from SCD patients (HbSS genotype) by applying 5 Pa shear stress with an ektacytometer (LORRCA). We evaluated RBC deformability before and after the application of shear stress. AC stimulation with Forskolin had distinct effects on RBC deformability depending on the application of 5 Pa shear stress. RBC deformability was increased by Forskolin before shear stress application but decreased after 5 Pa shear stress. AC inhibition with SQ22536 and protein kinase A (PKA) inhibition with H89 increased RBC deformability before and after the shear stress application. Non-selective PDE inhibition with Pentoxifylline increased RBC deformability. However, modulation of the different PDE types had distinct effects on RBC deformability, with PDE1 inhibition by Vinpocetine increasing deformability while PDE4 inhibition by Rolipram decreased RBC deformability after the shear stress application. The effects of the drugs varied greatly between patients suggesting some could benefit from one drug while others not. Developing drugs targeting the AC signaling pathway could have clinical applications for SCD, but more researches with larger patient cohorts are needed to identify the differences in the responses of sickle RBCs.